2010
DOI: 10.1007/s10237-010-0240-8
|View full text |Cite
|
Sign up to set email alerts
|

The collagen fibril architecture in the lamina cribrosa and peripapillary sclera predicted by a computational remodeling approach

Abstract: The biomechanics of the optic nerve head is assumed to play an important role in ganglion cell loss in glaucoma. Organized collagen fibrils form complex networks that introduce strong anisotropic and nonlinear attributes into the constitutive response of the peripapillary sclera (PPS) and lamina cribrosa (LC) dominating the biomechanics of the optic nerve head. The recently presented computational remodeling approach (Grytz and Meschke in Biomech Model Mechanobiol 9:225-235, 2010) was used to predict the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
127
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 50 publications
(72 reference statements)
10
127
1
Order By: Relevance
“…The predictions of this study are in good agreement with the measurements (Kankipati L, et al IOVS 2011;ARVO EAbstract 6255) 3,7,9-11 and predictions 14,19,23,29 of acute effects of IOP on the human ONH. Agoumi and colleagues 9 reported that for increases in IOP of about 12 mm Hg they observed LCD (with respect to Bruch's membrane) between -8 and 8 lm.…”
Section: Discussionsupporting
confidence: 78%
“…The predictions of this study are in good agreement with the measurements (Kankipati L, et al IOVS 2011;ARVO EAbstract 6255) 3,7,9-11 and predictions 14,19,23,29 of acute effects of IOP on the human ONH. Agoumi and colleagues 9 reported that for increases in IOP of about 12 mm Hg they observed LCD (with respect to Bruch's membrane) between -8 and 8 lm.…”
Section: Discussionsupporting
confidence: 78%
“…Hence, to preserve vision, it is important to characterize two elements central to connective tissues, namely the orientation and organization of the collagen fibers that form them [5,6]. Several techniques have been developed for measuring collagen fiber orientation and organization, including small angle light scattering [7,8], x-ray scattering [9][10][11][12], non-linear microscopy [7,13,14] and magnetic resonance imaging [15,16], or for estimating them using inverse numerical methods [17,18]. The complexity of the eye calls for a technique that provides data at multiple scales, including high resolution (micron-scale) and broad field of view (several mm to cm) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, inferiorsuperior and temporal-nasal preferential collagen orientation in the central cornea is possibly designed to resist the pulling forces of the extraocular recti muscles during eye movement and image fixation (Daxer & Fratzl, 1997;Boote et al, 2005), while circumferential collagen at the limbus may be required to withstand the increased stress brought about by the change in tissue curvature at the corneo-scleral border (Maurice, 1988;Boote et al, 2009). At the posterior pole, the existence of a collagen annulus in the peripapillary sclera (Pijanka et al, 2012) is structurally optimal for preventing excessive scleral canal expansion under elevated intraocular pressure and hence may provide a neuroprotective function for the optic nerve axons (Grytz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%